Decisional Dimensions in Expert Witness Testimony – A Structural Analysis - Biedermann, Alex; Kotsoglou, Kyriakos N. (Frontiers in Psychology, 2018)
The relationship between forensic science and legal adjudication is intricate mainly because the need to inform fact-finders on issues going beyond the layman’s knowledge poses challenges both on empirical and normative dimensions, in particular with regards to the specific role and duties of the different participants in the legal process. While rationality is widely upheld as one of the aspirations of the legal process across many modern jurisdictions, a pending question is how to remedy the uneasy relationship between general propositions (and knowledge claims) conditioning expert witness testimony, and individualized decisions taken by fact-finders. The focus has hitherto been put on the utilization of model-based and formal methods of reasoning while, regrettably, the concepts of judgment and decision-making have not received equal attention. A first aspiration of our paper will thus be to further clarify the nature of this systemic relationship in the particular area of the legal process involving scientific experts, by conducting a critical transversal analysis of current empirical, normative and doctrinal understandings of expert witness testimony. As a second aim, we will use this insight to argue in favor of the view that structural features of expert witness testimony are embedded in a decision-making process, and that the understanding of this decisional dimension is important for clarifying the respective roles of expert witnesses and fact-finders, and for favoring their mutual understanding thereof. To substantiate this perspective, and attest to its growing recognition as a frontier understanding, we will provide real-world examples from forensic science reporting practice and policy documents of professional bodies.